Community-acquired acute bacterial meningitis in adults: a clinical update. Issue 1 (26th September 2019) - Ellis, Jayne; Luintel, Akish; Chandna, Arjun; Heyderman, Robert S
Abstract: Background: Acute bacterial meningitis (ABM) in adults is associated with a mortality that may exceed 30%. Immunization programs have reduced the global burden; in the UK, declining incidence but persistently high mortality and morbidity mean that clinicians must remain vigilant. Sources of data: A systematic electronic literature search of PubMed was performed to identify all ABM literature published within the past 5 years. Areas of agreement and controversy: Clinical features cannot reliably distinguish between ABM and other important infectious and non-infectious aetiologies. Prompt investigation and empirical treatment are imperative. Lumbar puncture (LP) and cerebrospinal fluid microscopy, biochemistry and culture remain the mainstay of diagnosis, but molecular techniques are increasingly useful. The 2016 UK joint specialist societies' guideline provides expert recommendations for the management of ABM, yet published data suggest clinical care delivered in the UK is frequently not adherent. Anxiety regarding risk of cerebral herniation following LP, unnecessary neuroimaging, underutilization of molecular diagnostics and suboptimal uptake of adjunctive corticosteroids compromise management. Growing points: There is increasing recognition that current antibiotic regimens and adjunctive therapies alone are insufficient to reduce the mortality and morbidity associated with ABM. Areas timely for developing research: Research should be focused on optimization of vaccines (e.g. pneumococcal conjugate vaccines with extended serotype coverage), targeting groups at risk for disease and reservoirs for transmission; improving adherence to management guidelines; development of new faster, more accurate diagnostic platforms (e.g. novel point-of-care molecular diagnostics); and development of new adjunctive therapies (aimed at the host-inflammatory response and bacterial virulence factors).